The Development of Security and Whole Care System for the Aged in China (Springer Singapore, 2018)
This book examines the process of population aging in China and its unique features, considers the social progress implied in China becoming a society with an aging population, and assesses the tremendous risks and challenges involved. Based on the development of pension security systems around the world, the book studies the status quo and future requirements of the Chinese pension security system from the perspectives of capital, service and spirit, and puts forwards a three-pillar pension security system that is in conformity with China's current situation - and reflects the developmental trend that, in future, social security will likely transform from material security into comprehensive security. In addition, the book analyzes the Chinese pension security system. While integrating international perspectives, its main focus is on statistical analysis, combining theory with practice, and qualitative with quantitative analysis. As such, the book not only offers a "wi ndow" for the world on the status and evolution of China's pension security system, but also an opportunity for international academic dialogues.